Self-differentiation of countries' responsibilities: addressing climate change through intended nationally determined contributions - Kennedy Liti Mbeva; Pieter Pauw (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
As a result of the United Nations (UN) climate negotiations in Warsaw in 2013, all countries were invited to submit a climate action plan – or “Intended Nationally Determined Contribution” (INDC) – as part of the preparations for the 2015 UN climate summit in Paris (COP21). The innovation of this instrument lies in the fact that it is universal (each country formulates one) and that they are formulated “bottom-up” (countries set their own priorities and ambitions). In theory, this stimulates countries' self-differentiation of responsibilities and capabilities to address climate change. This paper analyses 159 INDCs on whether they advanced self-differentiation in the context of the notion of common but differentiated responsibilities and respective capabilities (CBDR-RC). The analysis focuses on aspects beyond mitigation targets, including INDC sections on fairness / equity as well as INDC content on adaptation and climate finance. Findings are provided for three country groupings: 15 “Annex I” parties, representing 42 countries (the EU, as one Party, represents 28 countries); 79 least-developed countries (LDCs) and small island developing states (SIDS), given the Paris Agreement's subtle differentiation towards these country groups; 65 “Middle countries” that fit neither category: a heterogeneous mixture of pre-dominantly middle-income countries. This paper offers two main conclusions: First, bottom-up setting of priorities and ambitions in INDCs advanced the issue of CBDR-RC beyond mitigation to include, at least, adaptation and finance. Although Annex I countries hardly mention adaptation in their INDCs, Middle countries, and LDCs and SIDS prioritise adaptation. The latter group, in particular, included adaptation plans and strategies. Climate finance was also hardly mentioned by Annex I countries. For Middle countries, however, and for LDCs and SIDS in particular, climate finance is often a condition for undertaking mitigation and adaptation. Second, self-differentiation through INDCs advanced the evolution of differentiation beyond the bifurcation of Annex I and non-Annex I countries. For example, the three country groupings introduced above have cascading priorities and ambitions in adaptation and finance. Such differentiation already appears in the Paris Agreement through “subtle differentiation”: flexible differentiation that is applicable to specific subsets of countries (e.g. the LDCs and SIDS) on certain issues (e.g. adaptation and finance) and procedures (e.g. timelines and reporting). The bottom-up formulation of INDCs brought many interesting insights about the climate politics and policies of years to come. However, as much as the instrument is universal, the limited guidance on the formulation of INDCs allowed for non-universal INDC content. For example, it is problematic that only the potential recipients included climate finance in their INDCs. Also, the adaptation challenge (e.g in terms of cost estimates and the global goal on adaptation that was decided upon in the Paris Agreement) remains unclear because developed countries did not include adaptation in their INDCs. We have used our in-depth analysis of the INDCs to create an interactive visualization of countries' policy priorities and ambitions. You can access the <link https://klimalog.die-gdi.de/en#INDCContentExplorer - external-link-new-window "Öffnet externen Link in neuem Fenster">INDC Content Explorer via the <link http://www.klimalog.info - external-link-new-window "Öffnet externen Link in neuem Fenster">Klimalog project page.
Keywords: 330; Klimawandel; Regionale + globale + transnationale Governance